An examination of the impact of initial founding conditions and decisions upon the performance of new bank start-ups - Bamford, Charles E; Dean, Thomas J; McDougall, Patricia P (Journal of Business Venturing, 2000)
Two schools of advice are often provided to fledgling entrepreneurial ventures: one advocates a deliberate and well structured phase prior to the beginning of operations, while the other suggests a quick-to-market approach that relies heavily upon the entrepreneurial team's ability to adjust resources and strategy as the new venture develops. Furthermore, the economy is generally seen as a short-term player in the success of the firm. That is, economic conditions appear to have a cyclical nature to them, so initial market conditions may only be relevant to the start-up speed of the new venture. Unfortunately, although there has been research that has examined the impact some of these areas may have, it has generally been limited to issues of survivability and/or has utilized young ventures (rather than new ventures). All of this leaves open the question of the long-term importance of these initial decisions and conditions. This research specifically examined a sample of new banks at the point of inception in order to accomplish the following: 1) to investigate the suggestion that initial founding conditions and decisions have a long lasting impact upon performance; 2) to gain an insight into the temporal endurance of these initial decisions and conditions by testing the extent to which the explanatory power persisted with time; and 3) to utilize multiple measures of performance in order to allow for a comparison of this important issue as it affects various aspects of a new venture's measurement of performance. The results of this study provide concrete suggestions for both those seeking to develop new ventures as well as those investing in them. First and foremost, initial founding decisions and conditions are significantly related to the growth potential of new ventures. In fact, those decisions and conditions were sufficient to explain a large amount of the variance in the growth of the new venture even six years after firm birth. The impact upon profitability was much less important, suggesting that while these initial decisions and conditions were important for predicting short-term profitability, they were not significant in later years. Second, the impact of initial founding decisions and conditions appears to diminish over time for at least two of our three performance measures. Not intuitively surprising, some research has suggested that the impact of these factors would not only persist but would actually amplify with time. Our research suggests that this may not be universally true. Third, we found that the results of our study varied (sometimes substantially) according to the measure of performance that was utilized. Uni-dimensional examinations of performance may mislead entrepreneurial teams and suggest that initial decisions/conditions may be more or less important depending upon the goals of the organization. The strong suggestion from this research is that considerable effort should be focused upon the initial decisions of the new venture as well as the market conditions at the inception of the venture.